2012
DOI: 10.1089/dna.2011.1332
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the NAD(P)H: Quinine Oxidoreductase 1 Gene 609 C>T Polymorphism with Esophageal Cancer Risk

Abstract: Association between the NAD(P)H: quinine oxidoreductase 1 (NQO1) gene 609 C>T polymorphism and esophageal cancer (EC) has been widely evaluated; however, the results are often irreproducible. We thus aimed to comprehensively evaluate this association through a meta-analysis. Data were extracted from 10 study populations involving 1390 EC patients and 1812 controls, and were analyzed using STATA software. Random-effects model was applied irrespective of between-study heterogeneity, which was assessed by the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(32 reference statements)
0
3
1
Order By: Relevance
“…In previous meta-analysis study, Wang et al (2012) and his colleagues' meta-analysis study also showed that the NQO1 gene 609 C> T polymorphism might contribute to esophageal cancer occurrence, especially in Eastern Asians, but in our study, no significantly different was observed in Caucasians or Asians. For colorectal cancer, no significant associations were found between NQO1 DOI:http://dx.doi.org/10.7314/APJCP.2013.14.4.2349 NQO1 C609T Gene Polymorphism andDigestive Tract Cancer: A Meta-analysis C609T polymorphism and colorectal cancer risk, but in the subgroup analysis by ethnicity; significant associations were observed for colorectal cancer in Caucasians, which was similar with previous meta-analysis study (Zhou et al, 2011;Chen et al, 2012).…”
Section: Discussioncontrasting
confidence: 64%
“…In previous meta-analysis study, Wang et al (2012) and his colleagues' meta-analysis study also showed that the NQO1 gene 609 C> T polymorphism might contribute to esophageal cancer occurrence, especially in Eastern Asians, but in our study, no significantly different was observed in Caucasians or Asians. For colorectal cancer, no significant associations were found between NQO1 DOI:http://dx.doi.org/10.7314/APJCP.2013.14.4.2349 NQO1 C609T Gene Polymorphism andDigestive Tract Cancer: A Meta-analysis C609T polymorphism and colorectal cancer risk, but in the subgroup analysis by ethnicity; significant associations were observed for colorectal cancer in Caucasians, which was similar with previous meta-analysis study (Zhou et al, 2011;Chen et al, 2012).…”
Section: Discussioncontrasting
confidence: 64%
“…It has been reported that the NQO1 C609T polymorphism is associated with the risk of many types of malignancies, such as cancers of the stomach [26], breast [27] and esophagus [28]. However, a meta-analysis by Guo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Animal models using the NQO1-knockout mice suggested that the NQO1 gene deficiency increased susceptibility to cancer (Long et al, 2000;Iskander et al, 2005). Recently, an exonic polymorphism, C609T (also known as Pro187Ser) in NQO1 gene has been identified and widely evaluated in various malignancies such as esophageal cancer (Wang et al, 2012), Leukemia (Han et al, 2013) and Bladder…”
Section: Introductionmentioning
confidence: 99%